Synthesis, Physicochemical and Biological Study of Gallium-68- and Lutetium-177-Labeled VEGF-A165/NRP-1 Complex Inhibitors Based on Peptide A7R and Branched Peptidomimetic - Katarzyna Masłowska; Ewa Witkowska; Dagmara Tymecka; Paweł Krzysztof Halik; Aleksandra Misicka; Ewa Gniazdowska (MDPI AG, 2022)
Neuropilin-1 (NRP-1) is a surface receptor found on many types of cancer cells. The overexpression of NRP-1 and its interaction with vascular endothelial growth factor-165 (VEGF165) are associated with tumor growth and metastasis. Therefore, compounds that block the VEGF165/NRP-1 interaction represent a promising strategy to image and treat NRP-1-related pathologies. The aim of the presented work was to design and synthesize radioconjugates of two known peptide-type inhibitors of the VEGF165/NRP-1 complex: A7R peptide and its shorter analog, the branched peptidomimetic Lys(hArg)-Dab-Pro-Arg. Both peptide-type inhibitors were coupled to a radionuclide chelator (DOTA) via a linker (Ahx) and so radiolabeled with Ga-68 and Lu-177 radionuclides, for diagnostic and therapeutic uses, respectively. The synthesized radioconjugates were tested for their possible use as theranostic-like radiopharmaceuticals for the imaging and therapy of cancers that overexpress NRP-1. The obtained results indicate good efficiency of the radiolabeling reaction and satisfactory stability, at least 3t1/2 for the 68Ga- and 1t1/2 for the 177Lu-radiocompounds, in solutions mimicking human body fluids. However, enzymatic degradation of both the studied inhibitors caused insufficient stability of the radiocompounds in human serum, indicating that further modifications are needed to sufficiently stabilize the peptidomimetics with inhibitory properties against VEGF165/NRP-1 complex formation.